Applying Positive End-Expiratory Pressure During Mechanical Ventilation Causes Pulmonary Redox Imbalance and Inflammation in Rats. Issue 5 (November 2018) - Andrade, Mônica C.; Souza, Ana Beatriz F. de; Horta, Jacques G.; Paula Costa, Guilherme de; Talvani, André; Cangussú, Sílvia D.; Menezes, Rodrigo C. A. de; Bezerra, Frank S.
ABSTRACT: Background: Mechanical ventilation (MV) may induce or aggravate lung injury through the production of cytokines, inflammatory infiltration of neutrophils, and changes in the permeability of the alveolar-capillary barrier. The use of positive end-expiratory pressure (PEEP) helps improve gas exchanges avoiding alveolar collapse at the end of expiration. The present study aimed to analyze inflammatory response and redox imbalance in lungs of rats submitted to MV with and without PEEP. Methods: Eighteen Wistar rats were divided into three groups: control (CG), PEEP group (PG), and zero PEEP (ZEEP) group (ZG). PG and ZG were submitted to MV for 60 min with or without PEEP, respectively. Subsequently, the animals were euthanized, and blood, bronchoalveolar lavage fluid, and lungs were collected for analyses. Results: The number of neutrophils was higher in PG compared with CG. Leucocyte and neutrophil influx in bronchoalveolar lavage fluid was higher in PG compared with CG. PG showed an increase in alveolar area compared with the other groups. There were increases in the levels of chemokines, CCL3 and CCL5, in PG compared with CG. There were increases in oxidation of lipids and proteins in PG compared with other groups. There were increases in the activity of superoxide dismutase and catalase in PG compared with CG and ZG. However, there was a decrease in the ratio of glutathione to glutathione disulfide in PG compared with other groups. Conclusions: MV with PEEP caused redox imbalance and inflammation in lungs of healthy rats.